Implementasi Pemutihan Pajak Kendaraan dan Respons Wajib Pajak di SAMSAT Surabaya Barat - Ryan Ditra Wirayudha; Rahma Ulfa Maghfiroh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the implementation of the motor vehicle tax amnesty program and taxpayer responses to the policy at the West Surabaya SAMSAT office. The tax amnesty program is viewed as a strategic fiscal policy designed not only to increase regional revenue but also to ease the financial burden on the public, particularly among lower-income groups. This research employs a qualitative method with a descriptive approach to gain an in-depth understanding of the implementation process and policy impacts. Data were collected through in-depth interviews with SAMSAT officials and taxpayers, direct field observations, and document analysis. The data were analyzed using the Miles and Huberman interactive model, supported by source triangulation to ensure validity. The findings indicate that the implementation was supported by digital service innovations such as SMS Push and WhatsApp Push, incentives including fine elimination and an Umrah lottery, as well as law enforcement strategies like joint operations and layered warning letters. Overall, taxpayer responses were positive, as reflected in increased compliance, although potential moral hazard may arise if the program is implemented repeatedly.